Empiric deworming and CD4 count recovery in HIV-infected Ugandans initiating antiretroviral therapy. - Alexander J Lankowski; Alexander C Tsai; Michael Kanyesigye; Mwebesa Bwana; Jessica E Haberer; Megan Wenger; Jeffrey N Martin; David R Bangsberg; Peter W Hunt; Mark J Siedner (Public Library of Science (PLoS), 2014)
BACKGROUND There is conflicting evidence on the immunologic benefit of treating helminth co-infections ("deworming") in HIV-infected individuals. Several studies have documented reduced viral load and increased CD4 count in antiretroviral therapy (ART) naïve individuals after deworming. However, there are a lack of data on the effect of deworming therapy on CD4 count recovery among HIV-infected persons taking ART. METHODOLOGY/PRINCIPAL FINDINGS To estimate the association between empiric deworming therapy and CD4 count after ART initiation, we performed a retrospective observational study among HIV-infected adults on ART at a publicly operated HIV clinic in southwestern Uganda. Subjects were assigned as having received deworming if prescribed an anti-helminthic agent between 7 and 90 days before a CD4 test. To estimate the association between deworming and CD4 count, we fit multivariable regression models and analyzed predictors of CD4 count, using a time-by-interaction term with receipt or non-receipt of deworming. From 1998 to 2009, 5,379 subjects on ART attended 21,933 clinic visits at which a CD4 count was measured. Subjects received deworming prior to 668 (3%) visits. Overall, deworming was not associated with a significant difference in CD4 count in either the first year on ART (β = 42.8; 95% CI, -2.1 to 87.7) or after the first year of ART (β = -9.9; 95% CI, -24.1 to 4.4). However, in a sub-analysis by gender, during the first year of ART deworming was associated with a significantly greater rise in CD4 count (β = 63.0; 95% CI, 6.0 to 120.1) in females. CONCLUSIONS/SIGNIFICANCE Empiric deworming of HIV-infected individuals on ART conferred no significant generalized benefit on subsequent CD4 count recovery. A significant association was observed exclusively in females and during the initial year on ART. Our findings are consistent with recent studies that failed to demonstrate an immunologic advantage to empirically deworming ART-naïve individuals, but suggest that certain sub-populations may benefit.